Strength of Cement Treated Base Courses in the Flexible Pavement Design for Pathlaiya- Nijgadh Section of East-West Highway of Nepal - KC, Narayan; Aryal, Rajendra; Joshi, Buddhi Raj; Shahi, Padma Bahadur (Himalayan Journal of Applied Science and Engineering, 2023)
Rutting and fatigue are the most common pavement distresses that are caused due to overloading, subgrade strength, and poor construction quality. The strength of the pavement layer can be improved by the construction of cement-treated layers. This study suggested that the cement-treated base is the effective modification technique for a granular base course by evaluating the unconfined compressive strength, and modulus of rupture. The unconfined compressive strength revealed that a cement-treated base is an effective treatment for the improvement of strength. Similarly, flexural strength indicated that a cement-treated base is an effective method to reduce the fatigue damage of the base course, and 5% cement content is sufficient to resist crack formation on the base course. 5.34% cement content in CTB developed a stiff mix with a stronger ability towards applied load dispersion that can resists deformation. In the meantime, unconfined compressive strength, modulus of rupture, and modulus of elasticity obtained at 5.34% cement content on a cement-treated base satisfied the minimum requirement as set by the Department of Roads, Government of Nepal.